Laboratory procedures for the isolation of chlamydia trachomatis from the human genital tract. Issue 11 (November 1975) - Reeve, P; Owen, J; Oriel, J D
Abstract : The technique of isolating Chlamydia trachomatis from the human gential tract by centrifuging clinical specimens on to cell monolayers with subsequent incubation has been improved and simplified. Gentamicin in the media was found to be superior to streptomycin in reducing bacterial contamination of specimens. The infectivity of chlamydial suspensions of laboratory cultured material was significantly reduced by storage at +4 degrees C for more than 48 hours, and by immediate freezing to -70 degrees C. When compared with immediate processing of the specimens, freezing to -70 degrees C was found to reduce the isolation rate of C.trachomatis from men with non-gonococcal urethritis (NGU) by approximately 20%. McCoy cells pretreated with idoxuridine were compared with irradiated McCoy cells for the isolation of C. trachomatis from clinical specimens. There was no significant difference in sensitivity between the two systems, but the former is considerably simpler. The effect of the centrifugal force used for inoculating specimens on to the cell monolayers on the isolation rate of C. trachomatis was studied in groups of men with NGU. Maximal isolation rates were obtained with forces of about 3000 G, which were not significantly raised by further increasing the force used. It is suggested that the isolation of C. trachomatis from the genital tract is now well within the capacity of any laboratory equipped with simple cell culture facilities.